2006
DOI: 10.1002/ajh.20597
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and prognosis of overt disseminated intravascular coagulation in a general hospital—Meaning of the ISTH score system, fibrin monomers, and lipoprotein–C-reactive protein complex formation

Abstract: The meaning, the utility, and the prognostic significance of the International Society of Thrombosis and Hemostasis overt disseminated intravascular coagulation (DIC) score and other parameters of coagulation activation including soluble fibrin monomer complexes (SFMC), antithrombin and protein C consumption, and formation of lipoprotein-C-reactive protein (LP-CRP) complexes (MDA slope 1 and flag A2) were evaluated in 165 inpatients from a general hospital for whom DIC testing was required by the attending phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 20 publications
2
14
0
1
Order By: Relevance
“…It is notable that 28-day mortality was significantly lower in the intervention group (Table 2). Previous studies have demonstrated that mortality in septic patients with DIC is significantly higher than in those without DIC, and resolution of DIC is associated with a favorable outcome [30, 31]. In the present study, incidence of DIC was significantly lower after administration of XBJ injection, confirming that this drug is effective in improving short-term prognosis of severe septic patients with DIC.…”
Section: Discussionsupporting
confidence: 83%
“…It is notable that 28-day mortality was significantly lower in the intervention group (Table 2). Previous studies have demonstrated that mortality in septic patients with DIC is significantly higher than in those without DIC, and resolution of DIC is associated with a favorable outcome [30, 31]. In the present study, incidence of DIC was significantly lower after administration of XBJ injection, confirming that this drug is effective in improving short-term prognosis of severe septic patients with DIC.…”
Section: Discussionsupporting
confidence: 83%
“…JAAM DIC criteria demonstrate high sensitivity and specificity for the diagnosis of DIC(52), and all patients diagnosed with the JAAM criteria were further examined by the criteria of the International Society of Hemostasis and Thrombosis (ISTH) as overt DICs(53). The registry of the JSEPTIC DIC(54) study enrolled 3195 cases with severe sepsis/septic shock over a two-year interval between 2011-2013, with a critically ill population as demonstrated by high mean APACHE II scores (23.1 ± 8.7) and an overall in-hospital mortality rate of 34%.…”
Section: Pro: Coagulopathy Should Be a Therapeutic Target In Criticalmentioning
confidence: 99%
“…Disseminated intravascular coagulation (DIC) score was calculated according to the scoring system of the International Society on Thrombosis and Haemostasis (ISTH) (Table 1) [14, 15]. Calculation of the score has been validated using either D-dimer or fibrin degradation products (FDP) titer, assigning points based on the degree of increase: none, moderate, or severe coagulation disturbances [15, 16].…”
Section: Clinical Materials and Methodsmentioning
confidence: 99%
“…Calculation of the score has been validated using either D-dimer or fibrin degradation products (FDP) titer, assigning points based on the degree of increase: none, moderate, or severe coagulation disturbances [15, 16]. Since FDP titer is not available in our laboratory, we had to modify the score by using D-dimer.…”
Section: Clinical Materials and Methodsmentioning
confidence: 99%